Enterococcus faecalis Bacteriophage vB_EfaS_efap05-1 Targets the Surface Polysaccharide and ComEA Protein as the Receptors - Huang, Lingqiong; Guo, Wenqiong; Lu, Jiahui; Pan, Wuliang; Song, Fuqiang; Wang, Peng (Frontiers in Microbiology, 2022)
Enterococcus faecalis is a Gram-positive opportunistic pathogen that causes nosocomial infections in humans. Due to the growing threat of antibiotic resistant E. faecalis, bacteriophage therapy is a promising option for treating E. faecalis infection. Here, we characterized a lytic E. faecalis bacteriophage vB_EfaS_efap05-1 with a dsDNA genome of 56,563 bp. The phage efap05-1 is a Saphexavirus with a prolate head and a tail and belongs to Siphoviridae. Efap05-1 uses either exopolysaccharide or membrane protein ComEA as the receptor because the mutation of both genes (ComEA and UDP-glucose 4-epimerase galE) prevents phage adsorption and leads to phage resistance, and complementation of ComEA or galE could recover its phage sensitivity. Our results provided a comprehensive analysis of a new E. faecalis phage and suggest efap05-1 as a potential antimicrobial agent.